The French commercial movement in the state of Aleppo in the Eighteenth century - عثمان, ربيع (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
The research deals with the French commercial movement in the stste of Aleppo in the eighteenth century , reviewing the commercial activity of the French community that settled in the city of Aleppo a long time ago and was active in the commercial fields. There are many French merchants who resided in the city of Aleppo and worked in trade between the city of Aleppo and Europe and they benefited from they city`s location and commercial importance one the international trade routes between East and West . This is what helped them to export the various oriental products in Aleppo to Europe , given the great strategic and commercial importance of Aleppo, taking advantage of its important commercial location , which made it acommercial center frequented by trade convoys coming from China and India and Persia , Iraq and Arabian Peninsula . In Aleppo and its market, many oriental products and goods were exported to Europe , and to in came the manufactured goods in Europe , which were marketed to various regions in the East . Thanks to this trade movement, Aleppo became one of the most important economic centers in the Ottoman Sultanate .